Molecular and spatial analysis of tertiary lymphoid structures in Sjogren’s syndrome - Nayar, S; Turner, JD; Asam, S; Fennell, E; Pugh, M; Colafrancesco, S; Berardicurti, O; Smith, CG; Flint, J; Teodosio, A; Iannizzotto, V; Gardner, DH; et al. (Nature Research, 2025)
Tertiary lymphoid structures play important roles in autoimmune and non-autoimmune conditions. While many of the molecular mechanisms involved in tertiary lymphoid structure formation have been identified, the cellular sources and temporal and spatial relationship remain unknown. Here we use combine single-cell RNA-sequencing, spatial transcriptomics and proteomics of minor salivary glands of patients with Sjogren’s disease and Sicca Syndrome, with ex-vivo functional studies to construct a cellular and spatial map of key components involved in the formation and function of tertiary lymphoid structures. We confirm the presence of a fibroblast cell state and identify a pericyte/mural cell state with potential immunological functions. The identification of cellular properties associated with these structures and the molecular and functional interactions identified by this analysis may provide key therapeutic cues for tertiary lymphoid structures associated conditions in autoimmunity and cancer.